Toxoplasma gondii: Infection natural congenital in cattle and an experimental inoculation of gestating cows with oocysts - Nogueira Costa, Gustavo Henrique [UNESP]; da Costa, Alvimar Jose [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; Saraiva Bresciani, Katia Denise [UNESP]; dos Santos, Thais Rabelo [UNESP]; Esper, Cesar Roberto [UNESP]; Santana, Aureo Evangelista [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Two studies, of a natural infection and an experimental infection, were performed in order to study congenital transmission of Toxoplasma gondii in cattle. In the first study, 50 fetuses were harvested from gestating cows that were eutanasied at a municipal slaughterhouse in Jaboticabal, São Paulo state, Brazil. In the second study, 11 gestating cows were divided into four groups for inoculation with T. gondii: GI consisted of three cows inoculated with 1.0 x 10(5) oocysts during their first trimester of gestation; GII consisted of three cows inoculated with 1.0 x 10(5) oocysts during their second trimester of gestation; GIII consisted of three cows inoculated with 1.0 x 10(5) oocysts during their last trimester of gestation; and GIV consisted of two control cows, one during its first and the other during its second trimester of gestation. In both studies, the presence of T. gondii was confirmed both indirectly by immunofluorescence assay (IFAT). In the natural infection experiment, 18% (9/50) of the gestating cows were confirmed to have specific antibodies (IFAT - 1:64) against T. gondii. The bioassay was able to diagnose the presence of T. gondii in the tissue samples from three calves. In the second experiment, the nine cows from groups I, II and III presented with specific antibodies (IFAT) against T. gondii. In contrast, T. gondii could not be detected by IFAT, histopathological examination or the bioassay in any of the nine calves born to cows experimentally infected with T. gondii oocysts. Based on the results from both studies, we conclude that congenital infection of T. gondii in cattle, while infrequent, does occur naturally. The pathogenicity of the strain of T. gondii may influence the likelihood of this route of transmission. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cattle; Congenital transmission; Toxoplasma gondii